Māori Academic Challenges: Delivering Mātauranga Māori During COVID-19 - Te Momo, Fiona (Journal of Contemporary Issues in Education, 2022)
In March 2020, the COVID-19 pandemic disrupted academic educational programmes in universities across the world, including Aotearoa New Zealand. For Māori academics who implement mātauranga Māori as a pedagogy, it became theoretically and practically challenging teaching virtually and online. The Te Taha Tinana, of Te Whare Tapa Wha model, created by aDurie in 1984 (Health Navigator, 2022) regarding the four dimensions of well-being, focuses on the physical presence, physical embodiment, and physical behaviour. This could not be easily taught virtuality through a computer screen during COVID-19 lockdown. For Māori academics transitioning from teaching Mātauranga Māori in person to an online environment brought forth these challenges. The challenges re-emerged in August 2021 when New Zealand went into Level 4 lockdown overnight because of the new COVID-19 Delta Virus variant. In 2022, the Omicron variant caused many universities in Aotearoa New Zealand to continue their first semester teaching online.
Keywords: covid-19; education; mātauranga māori; political development; social development; whanaungatanga

Teaching Diversity, Advancing Democracy: Challenges for Citizenship Education in Aotearoa New Zealand - Tawhai, Veronica M.H. (The International Journal of Diversity in Organizations, Communities, and Nations: Annual Review, 2008)
The presence of diverse needs, interests and perspectives in society is a key measure of a healthy representative democracy. Learning about diversity, and how society provides for diversity, is therefore a valuable characteristic of citizenship education (Arthur and Davison, 2000; Berding and Miedema, 1998; Feinberg, Fields and Roberts, 1997). This paper presents the findings of recent research about citizenship education in Aotearoa (New Zealand). In particular, it explores what presence the notion of diversity has in New Zealand’s citizenship education programme (social studies). In New Zealand, the provisions for diversity are under constant political debate. This includes the provisions for indigenous political representation, such as the Maori parliamentary seats. The research utilized critical discourse analysis and content analysis methods. A review of the social studies curriculum revealed a strong focus on identity, culture and heritage in New Zealand, but an absence of material about how diversity is provided for in society. This includes the socio-political provisions for diversity in New Zealand’s democratic arrangements, such as guaranteed indigenous representation. The implications of this absence are discussed in terms of citizens’ understandings of democracy, equality, and the preparation of citizens to discuss these issues further.
Keywords: citizenship; civics; diversity; education; equality

Civics and citizenship education in Aotearoa New Zealand : multidimensional challenges. - Tawhai, V. M. H. (Social Educator, 2008)
This paper presents the findings of research about civics and citizenship education in Aotearoa New Zealand. Aspects of New Zealand's electoral system, such as the Maori representation, have long been the focus of political debate. This paper identifies the civics and citizenship education provided to New Zealand citizens about this debate. In New Zealand, civics and citizenship education is taught through the social studies curriculum. A review of the teaching units for social studies showed a considerable focus in New Zealand on aspects of citizenship such as identity, but an absence of material for civic knowledge such as the make-up of the electoral system. This absence includes a lack of material on the Maori electoral representation. These challenges are considered in context of the multidimensional citizenship model arising from the international Citizenship Education Policy Study (CEPS).
Keywords: civics; curriculum; education; māori electorates; political parties; political power; political socialisation

Māori education and principles of self-determination in the twenty-first century. - O’Sullivan, Dominic (Waikato Journal of Education, 2001)
This paper argues that self-determination to the greatest extent possible is a legitimate aspiration for Maori people. It is argued that in education this requires a philosophical and policy response more focused on Maori autonomy than can be provided within the bicultural framework that has lately informed Maori relationships with other actors in the education arena. The paper considers the place of kohanga reo, kura kaupapa Maori and wananga in relation to broader Maori aspirations for self-determination and discusses proposals that these aspirations be furthered through the establishment of a Maori Education Authority. It is also argued that opportunities for self-determination in New Zealand are compromised by the government's unwillingness to alter a tightly controlled centralised education market to provide genuine Māori autonomy over what type of education might be available and to what end.
Keywords: crown policy; education; rangatiratanga; self-determination

A Māori perspective of being and belonging - Rameka, Lesley (Contemporary Issues in Early Childhood, 2018)
Belonging and being are inextricably linked. From a M?ori perspective, belonging and being can be viewed through a number of interconnected historical and contemporary frames. One frame is derived from M?ori perceptions of the creation of the universe and genealogical relationships to the universe and everything in it. Another frame of belonging and being stresses increasingly diverse and complex positionings that require negotiation of radically different terrains of assumptions, behaviours, values and beliefs. This article explores two interrelated aspects of being and belonging from a M?ori perspective: whakapapa (?genealogical connections?) and whanaungatanga (?family relationships?). It discusses how each aspect has changed over time as a result of colonisation, urbanisation and western education, and identifies how the reflection of each has been transformed.
Keywords: belonging; colonisation; education; urbanisation; whakapapa; whanaungatanga

Whose citizenship anyway? - Godfery, Morgan (set: Research Information for Teachers, 2016)
Keywords: belonging; citizenship; education

Knowing their place: the political socialisation of Maori women in New Zealand through schooling policy and practice, 1867-1969 - Jenkins, Kuni; Matthews, Kay Morris (Women's History Review, 1998)
Nineteenth-century British missionaries and the colonial government in New Zealand adopted a policy of assimilation of Maori into Pakeha (European) culture through actively discouraging Maori language, belief systems and culture. Central to the goal of assimilation was a Native School policy which in particular, emphasised the ‘Europeanising’ of young Maori. Church-run schools for Maori, which were subsidised by the state, aimed to return young Maori to their homes to model a Christian Pakeha lifestyle. This article argues that it was Maori girls, rather than Maori boys who were viewed as critical agents of change in the transformation of Maori society and that the colonial curriculum they were taught led to a political socialisation of generations of Maori women.
Keywords: assimilation; christianity; education; identity; te reo māori; wāhine māori

Decolonizing politics with insights from Indigenous Studies - Bargh, Maria (Identities, 2022)
Keywords: colonisation; decolonisation; education; mātauranga māori; rangatiratanga; tikanga | indigenous law